Eksplorasi Pandangan Siswa terhadap Penggunaan Teknologi dalam Proses Pembelajaran di Era Digital - Salma Fatimah; Dina Salsabila; Ummi Amalia Al karim; Muhammad Aniq Nazhif (Lembaga Pengembangan Kinerja Dosen, 2024)
The use of technology in the learning process can have a positive impact on the student's understanding process, but it also certainly has obstacles. Therefore, it is necessary to explore how students view the use of technology in learning so that learning can be adjusted to their wishes. To find out, this study uses interview methods and data analysis using descriptive and qualitative methods. The results show that most students have a positive view of the integration of technology in learning and learning activities. Technology is considered to make it easier for students to find the material they want to learn and also make learning more efficient and interesting. Even so, students feel challenged and feel that with the existence of technology, there will be a gap between students that causes disparity and in limitations to technology ownership or internet access. In addition, students' preferences regarding the technology used vary greatly; some students prefer the use of technology in learning, such as videos or other interactive media.